2002
DOI: 10.1086/338863
|View full text |Cite
|
Sign up to set email alerts
|

Angular Momentum Profiles of Warm Dark Matter Halos

Abstract: We compare the specific angular momentum profiles of virialized dark halos in cold dark matter (CDM) and warm dark matter (WDM) models, using high-resolution dissipationless simulations. The simulations were initialized using the same set of modes, except on small scales, where the power was suppressed in WDM below the filtering length. Remarkably, WDM as well as CDM halos are well described by the two-parameter angular momentum profile of Bullock and coworkers, even though the halo masses are below the filter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…In this paper, we perform a series of very high resolution CDM and WDM N ‐body simulations with the specific aim of exploring the halo model ingredients in the ΛWDM scenario. Over the past decade, there have been a limited number of numerical simulation studies of non‐linear structure formation in the WDM model (Colombi, Dodelson & Widrow 1996; Moore et al 1999; Colín, Avila‐Reese & Valenzuela 2000; White & Croft 2000; Avila‐Reese et al 2001; Bode et al 2001; Bullock, Kravtsov & Colín 2002; Zentner & Bullock 2003; Colín, Valenzuela & Avila‐Reese 2008; Zavala et al 2009; Macciò & Fontanot 2010; Dunstan et al 2011; Lovell et al 2012; Viel et al 2011). In most of these previous studies, conclusions have been drawn from object‐by‐object comparison of a relatively small number of haloes simulated in boxes of typical size L = 25 h −1 Mpc.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we perform a series of very high resolution CDM and WDM N ‐body simulations with the specific aim of exploring the halo model ingredients in the ΛWDM scenario. Over the past decade, there have been a limited number of numerical simulation studies of non‐linear structure formation in the WDM model (Colombi, Dodelson & Widrow 1996; Moore et al 1999; Colín, Avila‐Reese & Valenzuela 2000; White & Croft 2000; Avila‐Reese et al 2001; Bode et al 2001; Bullock, Kravtsov & Colín 2002; Zentner & Bullock 2003; Colín, Valenzuela & Avila‐Reese 2008; Zavala et al 2009; Macciò & Fontanot 2010; Dunstan et al 2011; Lovell et al 2012; Viel et al 2011). In most of these previous studies, conclusions have been drawn from object‐by‐object comparison of a relatively small number of haloes simulated in boxes of typical size L = 25 h −1 Mpc.…”
Section: Introductionmentioning
confidence: 99%
“…Past research on the impact of the WDM hypothesis on the phenomenology of cosmic structures has primarily focused on small-scale phenomena [10,[28][29][30][31][32], although there are some notable studies of large-scale structures [23,33]. In short, these results show that halo abundances for masses below the free-streaming mass-scale are suppressed relative to CDM.…”
Section: Introductionmentioning
confidence: 99%
“…the axis ratios) have a weak dependence on mass and redshift (Bullock 2002; Kasun & Evrard 2005; Allgood et al 2006; Bett et al 2007). The spin parameter distribution is well described by a lognormal function which varies weakly with halo mass (Barnes & Efstathiou 1987; Warren et al 1992; Cole & Lacey 1996; Bullock, Kravtsov & Colín 2002; Bett et al 2007). Bullock et al (2001) also found that the cumulative mass distribution of specific angular momentum j is well fitted by a universal function.…”
Section: Introductionmentioning
confidence: 99%